International Orthopaedics journal: A bibliometric analysis during 1977-2022 - Vaishya, Raju; Gupta, Brij Mohan; Kappi, Mallikarjun; Vaish, Abhishek (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. We aimed to examine the current research trends published by the International Orthopaedics (INOR) journal using bibliometric analysis. Design/Methodology/Approach. Using the Scopus database, we have retrieved all articles published by the International Orthopaedics journal from 1977 to 2022. The key players, such as countries, institutes, and authors, were identified, and their collaborative linkages were analyzed using MS Excel and VOSviewer software. Results/Discussion. We identified 7645 publications from 107 countries, of which 40 were from Europe and 32 from Asia. The most contributing countries were China, Germany, and France. The Netherlands, Canada, and Switzerland were the most impactful countries regarding citations. Hospital Henri Mondor (France) and IRCCS Rizzoli Orthopaedic Institute (Italy) were the most productive organizations. The most cited organizations were Harvard Medical School (USA) and Klinikum der Universität München (Germany). The most productive authors were Hernigou P (n=91) and Scarlat MM (n=56), and the most cited ones were Mont MA and Rouard H. The most active research areas were “Fracture Fixation” (n=1189), “Hip Arthroplasty” (n=1129), and “Osteosynthesis” (n=754). Hip received the most attention (n=2008), followed by Knee (n=1548), Spine (n=775), and Shoulder (n=517). 128 (1.67%) papers received >100 citations (high-cited papers or HCP) with an average of 150.11 citations per paper (CPP). Giannoudis PV and Mont MA published the maximum number of HCP. Conclusion. INOR has become a popular destination for global Orthopaedic researchers and is publishing their research from all the continents. The total number of publications in it has been progressively increasing and is receiving a more significant number of citations, thus helping to improve the journal's ranking and reputation.